Silent victories the history and practice of public health in twentieth-century America - Ward, John W.; Warren, Christian (New York ; Oxford : Oxford University Press, 2007)
'Silent Victories' takes a unique approach in its exploration of ten major public health issues addressed in the 20th century: for each issue, leading scientists in the field trace the discoveries, practices and programs that reduced morbidity and mortality from disease and injury.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Public health -- United States -- History -- 20th century; Discoveries in science